Occurrence of Metopism in Dry Crania of Adult Brazilians. (4th August 2013) - da Silva, Ivan do Nascimento; Fernandes, Katharina Jucá de Moraes; Ramalho, Antônio José Casado; Bispo, Rodrigo Freitas Monte; Rodrigues, Célio Fernando de Sousa; Aragão, José Aderval
Abstract : The metopic suture is located between the tubercles of the frontal bone. There are divergences regarding the exact time at which it closes, which ranges from the first to the tenth year of life, although it may persist into adulthood. This study was conducted on 134 dry crania from adult Brazilians, of which 95 were male and 39 were female. These were available in the anatomy laboratories of higher education institutions in Maceió, AL, Brazil. All the crania were examined macroscopically with regard to the presence (metopism: M) on absence of the metopic suture. M was considered to be complete (Mc) when it continued uninterruptedly from the nasium to the bregma and incomplete (Mi) when it was not present over its entire length. It was observed that Mc was present in 4.48% (6/134) of the skull examined, of which 50% (3/134) were male and 50% (3/134) were female. An incomplete metopic suture was found in 5.22% (7/144) of the crania and more frequently among males (3.73%; 5/134). Among the crania with a metopic suture, the dolichocephalic type predominated (7.46%) in relation to brachycephalic crania (1.49%) and mesocephalic crania (0.74%). There was no predominance of metopism between the sexes, while an incomplete metopic suture was slightly more common among males.